2022
DOI: 10.1002/essoar.10512710.1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Comment on ``Stratospheric Aerosol Composition Observed by the Atmospheric Chemistry Experiment Following the 2019 Raikoke Eruption' by Boone et al.

Abstract: This is a comment on the Boone et al. (2022) article. The authors analyzed spaceborne observations of stratospheric aerosol in 2019-2020 . They concluded, the dominating aerosol type was volcanic sulfate aerosol. They critisized Raman lidar observations of Ohneiser et al. (2021) and Ansmann et al. (2021). These authors classified the aerosol as wildfire smoke. Boone et al. ( 2022) stated that this classification is wrong. In this article, we clearly show that the dominant aerosol type was wildfire smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 12 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…In a study of stratospheric aerosols in the Arctic following the eruption of the Raikoke volcano (Boone et al, 2022), referred to hereafter as the OP (original paper), it was reported that the observed aerosol type was almost exclusively sulfate, based on high resolution infrared measurements from the space-based Atmospheric Chemistry Experiment Fourier transform spectrometer (ACE-FTS). Ansmann et al (2024), referred to hereafter as the Comment, counter that the aerosol type was mostly smoke (at least 75% smoke as of October 2019), based on ground-based Raman lidar measurements in fall/winter of 2019-2020 in the latitude range 85-86°N (Ohneiser et al, 2021). Both studies claim unambiguous identification of aerosol type, which of course cannot be true.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of stratospheric aerosols in the Arctic following the eruption of the Raikoke volcano (Boone et al, 2022), referred to hereafter as the OP (original paper), it was reported that the observed aerosol type was almost exclusively sulfate, based on high resolution infrared measurements from the space-based Atmospheric Chemistry Experiment Fourier transform spectrometer (ACE-FTS). Ansmann et al (2024), referred to hereafter as the Comment, counter that the aerosol type was mostly smoke (at least 75% smoke as of October 2019), based on ground-based Raman lidar measurements in fall/winter of 2019-2020 in the latitude range 85-86°N (Ohneiser et al, 2021). Both studies claim unambiguous identification of aerosol type, which of course cannot be true.…”
Section: Introductionmentioning
confidence: 99%